TOURISM MARKETING: CONTEXT, CHALLENGES AND POTENTIAL - Palupi, Rety; Slavov, Micho (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p09, 2020)
Tourism is one of the leading and most dynamic sectors of the world economy, and for its rapid pace, it is recognized as the economic phenomenon of the century. Modern tourism is an increasingly intensive, business-oriented, and commercially organized group of activities, and tourism marketing is becoming ever more important for a destination’s competitiveness. In this context, our research aims to analyze and synthesize the challenges marketing of tourist destinations is facing. The approach taken in this paper is to assess the related literature and focus on the key points for future research on tourism marketing. We argue that destination marketing must lead to the optimization of the effects of tourism and the achievement of national tourism organizations' strategic goals. This paper contributes to marketing professionals and academics, pointing out the uniqueness of tourism marketing.